Deskripsi Pengetahuan Konseptual Matematis Siswa SMK pada Materi Sistem Persamaan Linear Tiga Variabel - Usman Mulbar; Rosidah; Asriwan (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This study aims to determine the mathematical conceptual knowledge of SMK students specifically for class X on the material of a three-variable system of linear equations. The type of research used is descriptive qualitative research. The indicators of conceptual knowledge used are recognizing examples and non-examples of concepts; interpreting models, symbols, signs, or terms used to represent concepts; manipulate ideas related to the use of multiple representations; and identify the principles related to the material of the three-variable system of linear equations. There are four research subjects, namely two students in the middle category and two students in the low category. The data collection technique used is interviews. The instruments used in data collection were conceptual knowledge test instruments and interview guidelines. The results showed that students in the medium category were only able to fulfill the indicators of interpreting models, symbols, signs, or terms used to represent concepts and identify principles related to the material of a three-variable linear equation system. Meanwhile, students in the low category are only able to fulfill the indicators of interpreting models, symbols, signs, or terms used to represent concepts and identify principles related to the material of a three-variable linear equation system.